Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13643-021-01576-x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of service user experience, clinical outcomes and service use associated with urgent care services that utilise telephone-based digital triage: a systematic review protocol

Abstract: Background Telephone-based digital triage is widely used by services that provide urgent care. This involves a call handler or clinician using a digital triage tool to generate algorithm-based care advice, based on a patient’s symptoms. Advice typically takes the form of signposting within defined levels of urgency to specific services or self-care advice. Despite wide adoption, there is limited evaluation of its impact on service user experience, service use and clinical outcomes; no previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(29 reference statements)
0
5
0
Order By: Relevance
“… 40 A more recent systematic review came to similar results. 41 Many studies highlighted waiting time as predictive of reduced patient satisfaction. 42–47 Two systematic reviews reported that satisfaction rates were lower when expectations of patients regarding the decision were not met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 A more recent systematic review came to similar results. 41 Many studies highlighted waiting time as predictive of reduced patient satisfaction. 42–47 Two systematic reviews reported that satisfaction rates were lower when expectations of patients regarding the decision were not met.…”
Section: Discussionmentioning
confidence: 99%
“… 42–47 Two systematic reviews reported that satisfaction rates were lower when expectations of patients regarding the decision were not met. 41 48 49 Some studies saw patient satisfaction with the triage to be predictive of the compliance with the decision. 31 …”
Section: Discussionmentioning
confidence: 99%
“…14 See online supplemental appendix 1 for the PRISMA checklist. 15 Patient and public involvement No patient and public involvement (PPI) directly fed into the development or conduct of this review.…”
Section: Methodsmentioning
confidence: 99%
“…The literature has focused on certain performance aspects of telephone triage, such as experience of service [ 2 , 18 ], quality of communication [ 2 , 4 , 19–23 ], safety [ 2 , 5 , 19 , 24–29 ] or efficiency [ 5 , 19 , 20 ]. In addition, four literature reviews have been published [ 18 , 19 , 24 , 26 ]. Boggan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sexton et al. (2021) focused on evaluating telephone triage from the viewpoints of service user experience, service use, and clinical outcomes [ 18 ] describing the characteristics of patients accessing telephone triage services, the type of advice received, and the patient’s telephone triage experience. Gustafsson and Eriksson (2020) identified factors that indicate quality in telephone nursing.…”
Section: Introductionmentioning
confidence: 99%